Marketing management: A customer-centric approach - Selnes, Fred; Lanseng, Even J. (New Delhi Sage, 2025)
Marketing management is the process of planning, implementing, and controlling marketing activities to achieve organizational goals. It involves understanding customer needs, developing strategies for products and services, setting prices, promoting them through various channels, and analyzing results to ensure goals are met profitably.